As construções [V1andar+V2gerúndio] e [V1estar+V2gerúndio] no português do Brasil\; : formas em variação? - Emanuele Garbero Lins Reis (2021)
This research aims at analizing the structures [V1WALK+V2GERUND] and [V1BE+V2GERUND] in relation to the aspectual notion that they express, from a diacronical framework, based on the perspectives of sociolinguistic variation, combined with theoretical questions regarding the concept of grammaticalization, construction and verbal category, more especifically the aspect category (Cf. CASTILHO, 1968; KURYŁOWICZ, 1975[1965]; COMRIE, 1976; LEHMANN, 1982; TRAVAGLIA, 1985; HOPPER e TRAUGOTT, 1993; GOLDBERG, 1995; COSTA, 2002; BYBEE, 2003). Making use of a qualitative- quantitative of 600 (six hundred) ocurrences collected from Portuguese Corpus database, organized by Mark Davies (2006), the following hyphothesis was tested, that those two structures are variation forms in the codification of the duration aspect from Brazilian Portuguese, which could be a sign that the origin of the grammaticalization process from the two aspectual auxiliaries would be the linking verb. The results confirm the hypothesis that the auxiliary verbs walk and be, which connect to the gerund noun form to translate the intern time of an event. derive from linking forms, setting up a grammaticalization process from [-grammatical] to [+gramatical]. However, it was not possible to test the variation and ocurrence between the structures [V1WALK+V2GERUND] and [V1BE+V2GERUND] in aspect marking, since despite the fact that both mark the imperfective and cursive aspect, only the structure in which the auxiliary verb is walk marks iterativity. The cases in which the variation between both structures were tested are restrict to three contexts: (i) presence of time adverbial expression, (ii) auxiliary conjugated in past perfect and (iii) lexical structures.